CONTEMPORARY ISSUES IN DIVERSIFICATION OF NIGERIAN ECONOMY THROUGH ENTREPREURSHIP. - Akpomujere, Ovwiroro (Journal of Technology Management and Business, 2017)
This study examined the challenges and improvement strategies in the diversification of Nigerian economy through entrepreneurship. Two research questions and hypotheses guided the study. The population of the study was 183 registered Small and Medium Scale Enterprises (SMEs) in Warri Delta State. Simple random sampling was use to select 91 SMEs owners. The instrument for data collection was a questionnaire which was validated by 3 lecturers. The reliability of the instrument was .75 which was obtained using Pearson’s correlation technique. Data were collected through the aid of 15 research assistants. Data collected were analysed using mean for research questions and t-test for hypotheses. The study revealed that various challenges affect the diversification of Nigerian economy through entrepreneurship which include: low capital, poor access to loan, over taxation, inadequate infrastructural facilities, and poor transportation system amongst others. Hence, it was recommended that government and financial institutions in Nigeria should continuously support SMEs in Nigeria through the provision of better and efficient policies and support for SMEs to thrive for economic diversification.